The Multidisciplinary Swallowing Team Approach Decreases Pneumonia Onset in Acute Stroke Patients - Aoki, Shiro (PLoS One, 2016)
Dysphagia occurs in acute stroke patients at high rates, and many of them develop aspiration pneumonia. Team approaches with the cooperation of various professionals have the power to improve the quality of medical care, utilizing the specialized knowledge and skills of each professional. In our hospital, a multidisciplinary participatory swallowing team was organized. The aim of this study was to clarify the influence of a team approach on dysphagia by comparing the rates of pneumonia in acute stroke patients prior to and post team organization. All consecutive acute stroke patients who were admitted to our hospital between April 2009 and March 2014 were registered. We analyzed the difference in the rate of pneumonia onset between the periods before team organization (prior period) and after team organization (post period). Univariate and multivariate analyses were performed using a Cox proportional hazards model to determine the predictors of pneumonia. We recruited 132 acute stroke patients from the prior period and 173 patients from the post period. Pneumonia onset was less frequent in the post period compared with the prior period (6.9% vs. 15.9%, respectively; p = 0.01). Based on a multivariate analysis using a Cox proportional hazards model, it was determined that a swallowing team approach was related to pneumonia onset independent from the National Institutes of Health Stroke Scale score on admission (adjusted hazard ratio 0.41, 95% confidence interval 0.19–0.84, p = 0.02). The multidisciplinary participatory swallowing team effectively decreased the pneumonia onset in acute stroke patients.